"Giving" and "responding" differences in gestural communication between nonhuman great ape mothers and infants. Issue 3 (April 2017) - Schneider, Christel; Liebal, Katja; Call, Josep
Abstract: In the first comparative analysis of its kind, we investigated gesture behavior and response patterns in 25 captive ape mother–infant dyads (six bonobos, eight chimpanzees, three gorillas, and eight orangutans). We examined (i) how frequently mothers and infants gestured to each other and to other group members; and (ii) to what extent infants and mothers responded to the gestural attempts of others. Our findings confirmed the hypothesis that bonobo mothers were more proactive in their gesturing to their infants than the other species. Yet mothers (from all four species) often did not respond to the gestures of their infants and other group members. In contrast, infants "pervasively" responded to gestures they received from their mothers and other group members. We propose that infants' pervasive responsiveness rather than the quality of mother investment and her responsiveness may be crucial to communication development in nonhuman great apes.